MORAL VALUES IN EDUCATION: TEACHING ENGLISH CLASSROOM AT MA’HAD TAHFIZUL QUR’AN RAHMATULLAH SAMARINDA - ariyanti ariyanti (Teacher Training and Education Faculty, Widya Gama Mahakam Samarinda University, 2016)
It is obvious that moral values are values which always represent our daily lives. They reflect our activities wherever we are in society such as at school, at home, etc. In this article, the researcher tries to investigate the moral values directly to educational world by having the guideline of components of educational moral values proposed by Veugelers. This research is a descriptive qualitative study where the researcher describes in a very detail information regarding with what moral values reflected in English classroom at Ma’had Tahfizul Qur’an Rahmatullah Samarinda. As a result, the researcher found that from five components of educational moral values, there are only one component which is Moral Politics which seldom appears during the teaching and learning process. In addition, the components of Value Transfer, Reflective Practitioner, Moral Sensitivity, and Dialogue and Participant appear in the most meetings in the classroom. From those findings, it can be concluded that the participant, where in this case is the English subject teacher, cares about the teaching of moral values to the students in the classroom by transfering good moral attitudes, having the students to be sensitive and responsible individuals, as well as facilitate the students to have group discussion and work in pairs to solve their problems in learning English together.